Implementation of Christian Religious Education in Instilling the Value of Christ's Love at SDN 26 Simpang-Hulu, West Kalimantan - Sumarno, Yuel; Fernando, Yehezkiel V. (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
Implementation of Christian religious education still lacks creativity in rural schools. Inland schools are an important asset for the nation's progress. The spearhead of the nation is education itself. This research aims to provide solutions for schools in rural areas to implement relevant and creative Christian religious education. This research used a qualitative method with a descriptive approach, and then the researcher interviewed one of the educators who teaches at SDN 26 Simpang Hulu, West Kalimantan. The results of the research found that (i) an educator's creativity provides a strong impetus for existing learning, (ii) Educators must also teach with a contextual approach, not just a textual one, and (iii) Implementation of Christian religious education can be carried out if an educator can provide learning without the existence of a GAP or dividing wall.